Mekanisme Penegakan Hukum Hak Asasi Manusia ASEAN: Studi Perbandingan Mekanisme Penegakan Hukum Hak Asasi Manusia ASEAN dan UE - Dwi Saputra, Rangga; Estyy Pratiwi, L.ya; Eric, Eric; Stansyah, Dedy (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
In ASEAN and the EU, there is a social problem that underlies a similar problem that occurred in ASEAN and the EU regarding the authority of regional human rights institutions in deciding a case of human rights violations. ASEAN also does not have an independent judicial institution that functions to enforce human rights law independently. These factors are certainly an obstacle in the enforcement and protection of human rights in ASEAN in particular. This is different from the EU which has a more integrative law enforcement mechanism. In terms of upholding and protecting human rights, the EU has the European Court of Human Rights (ECHR). The judicial institution has a function to ensure that the human rights of the EU people are not violated and give the EU community the right to be heard in court for cases of human rights violations experienced.